Arthroscopic cuff repair: footprint remnant preserving versus debriding rotator cuff repair of transtendinous rotator cuff tears with remnant cuff - Jae Min Lee; Jong-Hun Ji; Sang-Eun Park; Dongwhan Suh; Ki-Jeon Song (BMC Musculoskeletal Disorders, 2024)
Abstract Background In transtendinous full thickness rotator cuff tears (FTRCT) with remnant cuff, conventionally, cuff remnant of the greater tuberosity (GT) is debrided for better tendon to bone healing. However, larger cuff defect caused overtension on the repaired tendon. The purpose of this study was to compare the clinical outcomes and tendon integrity between remnant preserving and remnant debriding cuff repairs in the transtendinous FTRCT with remnant cuff. Methods From March, 2012 to October, 2017, a total of 127 patients who had the transtendinous FTRCT with remnant cuff were enrolled in this study. Rotator cuff tears were repaired arthroscopically, with patients divided into two groups: group I (n = 63), where rotator cuff remnants were preserved during the repair, and group II (n = 64), where the remnants were debrided during the repair. Clinical outcomes were assessed at the last follow-up (minimum 2 years) using the UCLA score, ASES score, SST score, Constant Shoulder score, and range of motion (ROM). The analysis of structural integrity and tendon quality was performed using the Sugaya classification on postoperative MRI scans at 8 months after surgery. Results At the final follow-up, UCLA, ASES, SST, and CS scores significantly improved from preoperative values to postoperative (all p < 0.05): UCLA (I: 19.6 ± 6.0 to 31.7 ± 3.2, II: 18.0 ± 5.7 to 31.5 ± 3.2), ASES (I: 54.3 ± 10.7 to 86.5 ± 12.5, II: 18.0 ± 5.7 to 85.8 ± 12.4), SST (I: 5.6 ± 2.8 to 10.2 ± 2.0, II: 5.0 ± 2.9 to 10.1 ± 2.5), CS (I: 74.0 ± 17.2 to 87.8 ± 9.7, II: 62.0 ± 19.2 to 88.3 ± 6.2). However, there were no significant differences between the two groups (p > 0.05). Also, remnant preserving cuff repair yielded significantly better tendon quality on postoperative MRI (p < 0.05). The incidence of re-tear (Sugaya’s Type IV and V) was not significantly different between the two groups (I:17% vs. II:19%; p = 0.053). Conclusions Remnant preserving rotator cuff repairs, which facilitate tendon-to-tendon healing, are superior in terms of tendon quality and are the preferred option for transtendinous FTRCT. Trial registration Retrospectively registered.